Key analytical indicators of successful implementation of strategic transformations in a construction enterprise - Horbach, M.; Hudov, V.; Movsesyan, A.; Makeiev , D. (Ways to Improve Construction Efficiency, 2024)
The article is devoted to the analysis of key analytical indicators that successfully implement strategic transformations in a construction enterprise. In a dynamic market environment, construction companies are achieving adaptation to new requirements, technological changes, environmental standards and increasing the efficiency of project management. To do this, it is necessary to use innovative strategies, focusing on analytical indicators that help assess the processes associated with the transformation of management and production structures. The article presents some main categories of indicators that allow assessing the effectiveness of the implementation of strategic changes, in particular financial indicators, such as profitability, economic value added (EVA), as well as operational indicators, such as the speed of project implementation, the level of resource utilization, labor productivity, as well as qualitative indicators that reflect customer satisfaction and the level of innovative solutions. Particular attention is paid to the impact of digital technologies on management processes in construction, such as the use of BIM, IoT, AI and big data, which can optimize resources and improve the quality of projects. Indicator analysis allows construction companies to better understand the effectiveness of strategy implementation, control processes and reduce risks that are presented during transformations. The implementation of these indicators in strategic management allows you to increase competitiveness and ensure sustainable development of construction companies. It is important not only to assess current results, but also to predict future changes based on the analysis of the data obtained. Technologies such as big data analytics and artificial intelligence make it possible to build accurate forecasts regarding the risks and profitability of projects, thereby increasing the strategic flexibility of enterprises. In addition, the integration of such tools into management processes allows construction companies to adapt to changes faster and improve interaction with key stakeholders, such as investors, contractors and customers.